Peningkatan Skill Santri Dayah Madinatuddiniyyah Jabal Nur melalui Kegiatan Ekstrakurikuler: Model dan Proses - Rahmah, Syarifah; Amanda, Riska Zulka (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2023)
This research aims to explore and analyze the roles and benefits of extracurricular activities in Dayah Madinatuddiniyyah Jabal Nur, Dewantara, North Aceh, in developing the skills of students. The research methodology involved observations, interviews, and document studies. Subsequently, the acquired data was analyzed through the following stages: data condensation, data presentation, and verification/conclusion. The research findings indicate that Dayah Madinatuddiniyyah Jabal Nur offers various types of extracurricular activities designed to enhance various aspects of student development, including physical, spiritual, leadership, and skills development. Each extracurricular program is overseen by teachers or religious instructors who assist students in nurturing their talents and creativity. The benefits of extracurricular activities encompass improved emotional behavior, academic achievement, social interactions, character development, and career readiness. Furthermore, extracurricular activities play a crucial role in honing students' skills, which can contribute to their career development. The implications of this research suggest that well-organized and sustainable extracurricular activities at Dayah Madinatuddiniyyah Jabal Nur have substantial potential for enhancing student development. The significance of proper planning, organization, implementation, and evaluation in extracurricular activities not only impacts student development but also academic achievements and career preparation.